Tracing Individual Experiences of Everyday Greenness: Initial Results from the SpaceLog Mobile App - Kremer, Dominik; Neuner, Andreas; Jelinski, Sarah; Stadlmeier, Anna; Schlieder, Christoph; Walker, Blake (GI_Forum, 2023)
In this paper, we introduce a conceptual shift in how to investigate visual greenness as an important factor for individual wellbeing and self-reported health in everyday mobilities. Making use of controlled vocabularies of emotions, we discuss earlier approaches to data collection in everyday environments. We developed a new mobile diary app to collect multi-modal data that would allow not only for statistical spatial analysis, but also for a deeper analysis of individual sense-making of experiences in specific locations. From a limited first test sample, we evaluated the added value of the data collection process by conducting explorative data analyses of the visual greenness in user-generated imagery. We found that, in general, our method is able to relate different types of greenness observed on site to different emotional tags.
Created from Fastlane, Scopus look-up
Keywords: greenspace; health geography; image analysis; self-reported health; VGI